Association of Enlarged Perivascular Spaces With Amyloid Burden and Cognitive Decline in Alzheimer Disease Continuum. (18th October 2022) - Jeong, Seong Ho; Cha, Jungho; Park, Mincheol; Jung, Jin Ho; Ye, Byoung Seok; Sohn, Young H.; Chung, Seok Jong; Lee, Phil Hyu
Abstract : Background and Objectives: To investigate the effects of enlarged perivascular space (EPVS) on amyloid burden and cognitive function in Alzheimer disease (AD) continuum. Methods: We retrospectively reviewed 208 patients with AD across the cognitive continuum (preclinical, prodromal, and AD dementia) who showed amyloid deposition on 18 F-florbetaben PET scans and 82 healthy controls. EPVSs were counted for each patient in the basal ganglia (BG), centrum semiovale (CSO), and hippocampus (HP) on axial T2-weighted images. Patients were then classified according to the number of EPVSs into the EPVS+ (>10 EPVSs) and EPVS– (0–10 EPVSs) groups for the BG and CSO, respectively. In terms of HP-EPVS, equal or more than 7 EPVSs on bilateral hemisphere were regarded as the presence of HP-EPVS. After adjusting for markers of small vessel disease (SVD), multiple linear regression analyses were performed to determine the intergroup differences in global and regional amyloid deposition and cognitive function at the time of diagnosis of AD continuum. A linear mixed model was used to assess the effects of EPVSs on the longitudinal changes in the Mini-Mental State Examination (MMSE) scores. Results: Amyloid burden at the time of diagnosis of AD continuum was not associated with the degree of BG-, CSO-, or HP-EPVS. BG-EPVS affected language and frontal/executive function via SVD markers, and HP-EPVS was associated with general cognition via SVD markers. However, CSO-EPVS was not associated with baseline cognition. A higher number of CSO-EPVS was significantly associated with a more rapid decline in MMSE scores (β = −0.58, standard error = 0.23, p = 0.011) independent of the amyloid burden. In terms of BG and HP, there was no difference between the EPVS+ and EPVS– groups in the rate of longitudinal decreases in MMSE scores. Discussion: Our findings suggest that BG-, CSO-, and HP-EPVS are not associated with baseline β-amyloid burden or cognitive function independently of SVD at the diagnosis of AD continuum. However, CSO-EPVS appears to be associated with the progression of cognitive decline in an amyloid-independent manner. Further studies are needed to investigate whether CSO-EPVS is a potential therapeutic target in patients with AD continuum.